Development of Physics E-book Integrating Local Potential of Lake Toba to Improve Students' Critical Thinking Skills - Pratiwi*, Ika; Kuswanto, Heru; Chen, Diki; Rahmat, Anggi Datiatur; Putri, Santri Adi; Hanindya, Yovita (Universitas Syiah Kuala, 2025)
This study aims to produce a Lake Toba physics e-book that is valid and feasible according to experts, suitable for use by teachers and students in physics learning, and effective in improving students' critical thinking skills. The methodology used in this research is research and development with the ADDIE (analyze, design, development, implementation, and evaluation) model. The research results indicate that the product is valid and feasible according to two expert validators in physics content and media, with content validity index and content validity ratio scores of 0.92 and 0.96. The average product score, compared to the ideal average score, falls into the very good category. Limited practicality testing by teachers and students yielded scores of 94.44% and 81.02%, placing the e-book in the very practical category. The effectiveness test of the product showed an increase in students' critical thinking skills by 0.55 and was included in the average category. Therefore, this product has great potential to be used by teachers and students in physics learning